PENGGALIAN TOPIK DAN FUNGSI IMAJINATIF DALAM WACANA CERITA ANAK DI MEDIA SOLOPOS DAN KOMPAS - Wahyudi, Agus Budi; Fatimah, Nuraini (Jurnal Penelitian Humaniora, 2012)
The objective of the research is to describe (1) fairy tale topic (2) the imaginative function, and (3) construct a narrative map based on extracting topic and imaginative function in a fairy tale at Solopos and Kompas newspaper. It used a descriptive-qualitative. The data sources were the fairy tales in Solopos and Kompas newspaper published from March to August 2022. The data consisted of 52 fairy tales (26 taken from Solopos and the others from Kompas. The objects of the study were the fairy tales in topics and imaginative function. The data analysis used a content analysis in combination with referential-equivalent method. The findings of the research show that (1) the fairy tales in Solopos and Kompas referred the topics to persona and non-persona, the constituents in words and phrases, nouns and verbs, and adverbs. The topical-sequential degree in Solopos and Kompas was very unique because they were generally not ?strict?. (2) The imaginative function that was found in the discourse of fairy tale in Solopos and Kompas on the March to August 2011, a total of ten 133, in the Solopos are 69, and in Kompass are 64 function of imagination. Every fairy tale discourse contains only one to four imaginative function, even that does not contain terms that have imaginative function. Narative map in this research, is built based the identification of the principal builders of the story elements (topic, character, and narrative structure) and role of imaginative function in each part of thefairy tale. The fairy tale sharing into three parts categorized, there are the beginning of the story (BAC), the center of the story (BTC), and the end of the story (BAKC).